Alphabet Soup: The Relationship between Multinationality and Firm Performance - O'Hagan Luff, Martha (My University, 2018)
We specifically address previously identified deficiencies in the multinationality-performance literature and show no evidence of a consistent relationship between a firm’s level of internationalisation and its performance by any metric for 803 companies from 11 European countries over a 19-year period from 1998-2016. We find that in many cases domestic firms outperform more international firms. We contribute both empirically and methodologically by using more accurate dynamic measures of multinationality, alternative financial and market based performance measures, and an extended geographic focus. We conclude that a firm’s degree of multinationality does not consistently affect performance either positively or negatively, and the competing “alphabet-soup” of shape-based multinationality-performance findings in the literature only serves to confirm our findings.
PUBLISHED
Keywords: Multinationality and performance; Globalisation; Internationalisation